[OP.1B.07] PRESERVED CEREBRAL AUTOREGULATION IN CLINICAL ALZHEIMER'S DISEASE DURING REPEATED ORTHOSTATIC MANEUVERS. (September 2017) - De Heus, R.; Witjes, B.; Sanders, M.; Oudegeest-Sander, M.; De Jong, D.; Claassen, J.
Abstract : Objective: Preclinical studies suggest early amyloid-related cerebrovascular abnormalities in Alzheimer's disease (AD) that impair neurovascular coupling and contribute to neurodegeneration. Hypertension could aggravate this process and is an important potential target for prevention of AD. However, in animal studies, vascular dysfunction in AD led to severely impaired cerebral autoregulation (CA), which could render antihypertensive treatment unsafe. We investigated CA during repeated orthostatic maneuvers in clinical AD compared to cognitively healthy controls (HC) and patients with mild cognitive impairment (MCI). Design and method: 35 patients with mild-to-moderate probable AD, 21 subjects with MCI and 35 HC, all >50 years, were included. Mean arterial pressure (MAP, Finapres) at the finger and mean cererbal blood flow velocity (MCBFV, Multi-Dop X4) at the middle cerebral artery were collected during repeated sit-to-stand maneuvers at a frequency of 0.05 Hz for 5 minutes. CA was quantified in the frequency domain by transfer function analysis (CARNet Matlab script version 1, 2016), and in the time domain by calculating the maximal change in MAP and MCBFV for each sit-to-stand maneuver expressed as absolute values and as percentage of mean MAP and MCBFV. Groups were compared using ANOVA (p < 0.05). Results: MCBFV was lower in AD (39.6 cm/s) compared to HC (45.1 cm/s, p = 0.033), with MCI subjects in between (41.1 cm/s). The repeated orthostatic maneuvers caused similarly large pertubations in MAP (22.4 mmHg for HC, 18.7 mmHg for MCI subjects and 20.7 mmHg for AD patients, p = 0.161). The absolute and relative changes in MCBFV were larger for HC (15.1 cm/s and 33.1%) compared to MCI subjects (9.7 cm/s and 23.7%, p = 0.002), but not compared to AD patients (11.7 cm/s and 29.9%). For TFA, the normalized gain was similar in HC (1.42 %/mmHg), MCI (1.17 %/mmHg) and AD (1.31 %/mmHg, p = 0.053). Conclusions: In this study we found no evidence for impaired cerebral autoregulation in AD patients for large (±20%) changes in MAP. This would suggest antihypertensive treatment to be safe in AD.